The use of big data analytics to discover customers’ perceptions of and satisfaction with green hotel service quality - Arıcı, Hasan Evrim; Arıcı, Nagihan Cakmakoglu; Altinay, Levent (Informa UK Limited, 2022)
This study examined customers’ green reviews on TripAdvisor and identified environmentally friendly themes and concepts. The differences among the 10 countries in terms of the volume of green reviews and customers’ green satisfaction ratings were also analyzed. Using Leximancer analysis and multivariate analysis of a big dataset, we adopted a mixed research method to analyze 121,780 reviews posted on TripAdvisor for 87 green hotels from the top 10 tourism countries. The Leximancer analysis found that the most important themes mentioned in customers’ green reviews are room, daily, hotel, staff, front, food, coffee, amazing, experience, and trip. The results also showed that highest satisfaction ratings were ranked in Italy, the USA, and Turkey, respectively, while the lowest ratings were from Germany and France. The results provide critical recommendations for hoteliers to truly comprehend what green practices are noticed and appreciated by their customers.
Keywords: 11. Sustainability